Paciente femenino de 22 años de edad con hernia hiatal grado i y gastritis crónica - Navarrete Avilés, Andreina (2018)
We present the case of a 22-year-old female patient, who came to the clinic because of pain in the epigastric region, morning ebb and asthenia, 3 months ago she was diagnosed with grade I hiatal hernia and chronic gastritis. The patient presents symptoms typical of the pathology, in the physical examination nothing that draws attention, its weight is normal according to the World Health Organization. Several studies have been conducted in Ecuador regarding the disease whose results show that there is an increased prevalence of gastritis and hernia in patients of 20 and 30 years due to exogenous and endogenous factors. Therefore objective that has been raised is to improve the symptoms presented by the patient and decrease the consumption of blockers, gastric receptors thus improving food intake and quality of life. Go to nutritional consultation for the assessment of nutritional status, a comprehensive anthropometric, biochemical, clinical and dietetic assessment is carried out whose results are poor dietary habits due to excess food intake in energy, a feeding plan, nutritional education, and recommendations according to their pathology, with which the symptoms of the patient are best achieved.